Velopharyngeal Dysfunction and Sleep Apnea-A Survey to Ascertain Surgical Practice Patterns. (January 2017) - Bennett, Katelyn G.; Robinson, Adina B.; Kasten, Steven J.; Buchman, Steven R.; Vercler, Christian J.
Objective: To determine if all cleft surgeons uniformly and adequately evaluate patients with cleft for obstructive sleep apnea (OSA) and consider OSA in treatment of velopharyngeal dysfunction (VPD). Design: A 22-question survey was administered via e-mail to 1117 surgeons who were members of the American Cleft Palate-Craniofacial Association. Logistic regression was used to determine if management was affected by years in practice, clinical volume, field of training, and region of practice. Main Outcome Measures: We sought to determine if years in practice, clinical volume, region of practice, and surgical specialty affected surgeons' evaluation of OSA and their approaches to VPD. Results: A total of 231 surgeons responded (21% response rate), and 67% stated that they had trained in plastic surgery. With increasing years of practice, surgeons were less likely to refer patients for preoperative and postoperative sleep studies ( P = .00 and P = .001, respectively), screen patients for sleep apnea ( P = .008), or change their management based on a sleep study ( P = .001). There were no significant differences in screening or testing for OSA based upon clinical volume. Among those surveyed, otolaryngologists were more likely to refer patients for postoperative sleep studies ( P = .028). Surgeons in the Southeast were more likely to change their management based upon a sleep study ( P = .038). Conclusions: Statistically significant trends in screening and testing for OSA in the setting of VPD were identified by this survey. Notably, older surgeons were less likely to investigate OSA in their patients, and not all specialties equally refer for postoperative sleep studies.